A rapid dual-drive technology for extinguishing large high-gas coal mines fires - Mei, Yong (Frontiers in Earth Science, 2023)
Fires formed by the high gas protrusion in coal mines are difficult and risky to extinguish during the mine closure process due to the mine's large closed range and underground gas stock. To achieve efficient and safe unsealing, reduce the risk of re-ignition and gas explosion, and accurately determine the fire extinguishing effect, a dual-drive rapid fire extinguishing technology is proposed. This technology involves ground precise positioning of drilling holes, rapid and large flow of liquid nitrogen injection, and curtain grouting to block fires in ultra-large high-gas mines. The practical results demonstrate that the implementation of surface injection of liquid nitrogen for fire extinguishing and cooling, and plugging effectively reduces the concentration of CO in the underground space from 230PPm to 0PPm, and decreases the CH4 concentration content from 90% to less than 0.75%. The fire extinguishing and cooling effect is fast and significant. A technical scheme for unsealing the fire area of the whole mine is formulated on a large scale based on the state of pumping and releasing pressure in the closed space of the mine. This scheme has important guiding significance for safety rescue and rescue operations after serious fire accidents occur in similar highgas prominent mines.